Occupational injuries and corporation liabilities - Ali Mohamed, Ashgar Ali; Ramalingam, Chithra Latha (Lexis Nexis Malaysia Sdn Bhd, 2021)
Where death or injury arises from workplace accidents, the dependents of the deceased or the injured worker would be entitled to compensation benefits which typically cover medical and/or end-of-life expenses and some level of lost income compensation. The compensation benefits under OSHA are medical benefits, disablement benefits and rehabilitation, while dependants for the deceased employees may receive dependants’ benefits, funeral benefit, education benefit. Where a claim falls under the OSHA the injured worker is barred from claiming for compensation or damages in the civil courts. It is equally important for the workers to take reasonable precaution of their own safety and health at the workplace and this includes avoiding acts or conducts which may adversely affect their own safety and health as well as others at workplace. Breach of this may lead to disciplinary action up and including dismissal. Despite the above, work-related accidents have been on the rise where it was reported that in 2020 more than 40,000 workers were involved in work-related accidents, an alarming figure which implies that the workplace safety awareness is lacking among employers. Hence, the corporation’s liability for compromising workplace safety and health is discussed herein with reference to decided cases